Combination of levenshtein distance and rabin-karp to improve the accuracy of document equivalence level - Putera Utama Siahaan, Andysah; Aryza, Solly; Hariyanto, Eko; ., Rusiadi; Hasudungan Lubis, Andre; Ikhwan, Ali; Len Eh Kan, Phak (International Journal of Engineering and Technology, 2018)
Rabin Karp algorithm is a search algorithm that searches for a substring pattern in a text using hashing. It is beneficial for matching words with many patterns. One of the practical applications of Rabin Karp's algorithm is in the detection of plagiarism. Michael O. Rabin and Richard M. Karp invented the algorithm. This algorithm performs string search by using a hash function. A hash function is the values that are compared between two documents to determine the level of similarity of the document. Rabin-Karp algorithm is not very good for single pattern text search. This algorithm is perfect for multiple pattern search. The Levenshtein algorithm can be used to replace the hash calculation on the Rabin-Karp algorithm. The hash calculation on Rabin-Karp only counts the number of hashes that have the same value in both documents. Using the Levenshtein algorithm, the calculation of the hash distance in both documents will result in better accuracy.Â Â